Access to digital information resources as a support to academic achievement - Vrana, Radovan (Array, 2014)
This paper presents results of the research of students at the Faculty of Humanities and Social Sciences (FHSS) in Zagreb, Croatia and their use of digital information resources. The results indicate tendency toward selection of digital information resources for use in their education ; the maturity in assessing quality of these digital information resources and the maturity in distinguishing the good and the bad sides of digital information resources including open access information resources. The results could be integrated into the process of selection of reading materials for the courses at the FHSS, now that students’ preferences are more clearly identified.